Crystal-storing histiocytosis in the stomach: A case report and review of the literature - Kong, Linghong; Xue, Liyan; Zhong, Yanfeng; Wang, Shenglan; Zheng, Danfeng; Wang, Lining; Jiao, Yang; Zhang, Xinpeng; Xue, Huizhong; Liu, Xiaogang (Frontiers in Oncology, 2022)
Crystal-storing histiocytosis (CSH) is a rare disorder characterized by the accumulation of non-neoplastic histiocytes that contain intracytoplasmic crystallized immunoglobulins. Although CSH can occur in various organs, gastric CSH is very rare. Therefore, diagnosing gastric CSH remains a challenge. Here, we present the case of a 69-year-old man with localized gastric CSH who presented with positive fecal occult blood for 2 days. Gastroscopy showed that there was a piece of irregular whitish focus in the big bend of the gastric antrum, which was soft and elastic. Histologically, the biopsied gastric mucosa showed chronic inflammation, mild activity with erosion, and numerous eosinophilic mononuclear cells containing fibrillary crystalloid inclusions in the lamina propria. Immunohistochemically, these crystal-containing cells were positive for CD68/PGM1 and Igk, which revealed that the cells were histiocytes harboring kappa light chain-restricted immunoglobulin crystals. Electron microscopic examination showed numerous high-electron-density particles in the cytoplasm of cells, with crystal structures of different sizes and shapes. This case highlights how immunohistochemistry can help with differential diagnosis and classification